Okupasi dolina kidang hunian prasejarah akhir plestosen - awal holosen kawasan Karst Blora - Okupasi_dolina_kidang_hunian_prasejarah_akhir_plestosen_-_awal_holosen_kawasan+Karst_Blora (Balai Arkeologi DIY, 2019)
st,1/irh,c.1